Answer:
y + 2 = 1 (x+3) ............> y + 2 = x + 3
Step-by-step explanation:
The general form of the equation of a line in point-slope form is:
y - y₁ = m (x - x₁)
where:
m is the slope of the line
(x₁ , y₁) is a point that belongs to the line
The general form of the equation of a line in slope-intercept form is:
y = mx + c
where:
m is the slope
c is the y-intercept
1- Getting the point:
We are already given the point (-3 , -2) so we'll directly use it
2- Getting the slope
We are given that our line is parallel to the line:
y = 1x - 7
We know that parallel lines have equal slopes
This means that:
slope of the line we want = 1
3- Getting the equation:
Substitute with the point and slope in the above form to get the equation
This is done as follows:
y - y₁ = m (x - x₁)
y - (-2) = 1 (x - (-3))
y + 2 = 1 (x + 3)
y + 2 = x + 3
Hope this helps :)